DASEIN: a celebration of caring science scholars in communion - Maykut, Colleen (My University, 2018)
I am proposing Communion, as the 7th C, vital for the development, nurturance, and expression of a holistic expression or being of Roach's (2002) caring attributes. I am defining communion as humbly entering each other's world—a shared journey of being in the world. As humans, our primary focus is on our potential—the possibility of authentic human expression, being in and concerning the world (Heidegger, 1962). I will explore the particular of Caring Sciences through my own professional "Dasein" as I attach meaning of my own reflective process to higher philosophical beliefs.
Keywords: caring; nursing science; interpersonal relations